Corporate Governance and Firm Performance: Evidence from Listed Malaysian Firms - Mohamad, Shafi; Adamu Pantamee, Abdurrahman; Chee Keong, Ooi; Wing Chong Garrett, Kwong (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the relationship between corporate governance and firm performance with the sample data of 180 listed companies in Malaysia during the period 2013-2017. This study employed Tobin’s Q and ROA as the proxies of firm performance, and ownership concentration, non-executive directors, and board size are employed as the proxies of corporate governance. The results show a significant association between corporate governance and firm performance when non-executive directors and board size are used as proxies of corporate governance, but not significant when ownership concentration is used as a proxy of corporate governance. This study contributes to the field of corporate governance and organizational performance as it was found that better corporate governance leads to high firm performance. Further, this study provides insight to regulators who are interested in improving governance in developing economies.